Electrodeposited ZnO nanoparticles on vertically aligned carbon nanotubes (VACNTs) as promising charge extracting electrodes for halide perovskite devices. Issue 5 (16th July 2020) - Belchi, Raphaëlle; Pibaleau, Baptiste; Pinault, Mathieu; Ratier, Bernard; Herlin-Boime, Nathalie; Bouclé, Johann
Abstract : This work presents an original nanostructured architecture for energy conversion applications based on vertically aligned carbon nanotubes (VACNTs). Abstract : This work presents an original nanostructured architecture for energy conversion applications based on vertically aligned carbon nanotubes (VACNTs). The developed approach consists in exploiting the directional charge transport provided by the VACNTs-based network to efficiently extract photo-generated electrons in perovskite solar cells. High density, 20 μm-long carpets of VACNTs were synthesised by an aerosol-assisted chemical vapor deposition (AACVD) process on aluminium substrates. The technique of electrodeposition, usually used for thin film elaboration, was adapted to decorate carbon nanotubes (CNTs) with ZnO nanoparticles (NPs) and reinforce the CNT scaffold. This procedure was successful even for the high CNT carpet density used here. Then, this dense nanostructured network was successfully infiltrated by a methylammonium lead iodide perovskite that crystallized homogeneously between the nanotubes and all along their length, from the bottom to the top. While this study is mainly focused on the material nano-engineering aspect, the charge extraction ability of the system was tested by photoluminescence spectroscopy. A quantitative luminescence quenching is demonstrated, evidencing an efficient charge transfer between the perovskite and the VACNTs/ZnO electrode. These promising results led to the fabrication of fully working devices that demonstrated a diode-like electrical response, characteristic of a solar cell in the dark. Considering both the possibility to develop this architecture at the industrial scale and the obtained physical properties, electrodes based on VACNTs decorated by ZnO NPs seem to be a relevant and promising candidate for efficient optoelectronic devices such as perovskite solar cells.